(untitled) (Economics and region, 2023)
The beginning of a full-scale war in Ukraine in 2022 radically changed the financial market environment, which requires effective and prompt adaptation of the capital structure management policy to new conditions. Ukrainian enterprises are forced to fast-track expenses and income provided in their own budgets, apply stabilization measures, look for new ways to profit and review current relations with existing partner enterprises. Another important factor that significantly affects the activities of Ukrainian enterprises is the uncertainty factor, that is, even with the maximum established work, it is impossible to level the impact of the deterioration of the current state of force majeure. This situation forces enterprises to significantly revise priorities and develop new programs of their own activities aimed at the short term, since this is more reliable. One of the most important issues for each enterprise is the regulation of the ratio of capital and its value, since the terms of use have changed significantly. This implies the feasibility of finding new tools or improving the use of existing ones, which is ultimately designed to optimize the structure of capital. To assess the current state of the capital structure, various indicators are designed that are indicators of the "health" of the enterprise. It is advisable to use indicators in a complex to obtain the most objective understanding of the situation. In turn, the optimization of the capital structure based on the use of the effect of financial leverage in the conditions of war is complicated by the increase in the cost of borrowed capital, the restriction of access to financial markets and a significant decrease in the financial results of Ukrainian enterprises, as shown in the article. The current directions of optimization of the capital structure in modern wartime conditions are outlined: reduction of the share of borrowed capital through negotiations with creditors, reduction of the cost of borrowed capital by re-crediting, increase of operating profitability and increase of efficiency of management of accounts receivable and accounts payable.